Handbook of Energy Engineering, Sixth Edition - Thumann, Albert; Mehta, D. Paul (Fairmont Press Taylor & Francis Group [distributor], 2008)
Covering the latest codes and standards and the Energy Independence and Security Act, this edition includes information on software packages from the Best Practices Program of the U.S. Department of Energy; and emerging technologies such as oxy-fuel combustion, high efficiency burners, enhanced heat exchangers, and ceramic membranes for heat recovery. This reference will guide you step by step in applying the principles of energy engineering and management to the design of electrical, HVAC, utility, process and building systems for both new design and retrofit projects. Topics covered include how to do an energy analysis of any system; electrical system optimization; state-of-the-art lighting and lighting controls; thermal storage; cogeneration; HVAC and building system optimization; compressed air systems; third party financing and much more. The text is thoroughly illustrated with tables, graphs, diagrams and sample problems.